Effect of addition of disodium EDTA to ceftriaxone and sulbactam on the susceptibility of gram-negative pathogens - Chaudhuri, Shreya; Gupta, Saurabh (International Journal of Research in Medical Sciences, 2023)
Background: Indiscriminate use of antibiotics has resulted in the emergence of resistant pathogens. Ethylenediaminetetraacetic acid (EDTA) is a well-known chelating agent. EDTA is also a potentiating and sensitizing agent when combined with antibiotics. Objectives of current study were to examine the antibacterial activity of Ceftriaxone+Sulbactam+ Disodium EDTA against pathogens isolated from urine, blood, and respiratory secretions (sputum, tracheal tube aspirates) and compare it with other antibiotics. Methods: The study was a retrospective study conducted in a tertiary care hospital between January 2019 and December 2019. Gram-negative isolates were obtained from clinical samples of urine, blood and respiratory samples were tested for susceptibility to different antibiotics and also for ESBL and MBL production Results: Respiratory isolates: Against Acinetobacter baumannii, 64% of isolates were sensitive to Ceftriaxone Sulbactam EDTA. Highest resistance rates were observed with Piperacillin tazobactam, amoxicillin clavulanate and Cefoperazone+Sulbactam. All Clinical isolates of Pseudomonas were sensitive to Ceftriaxone Sulbactam EDTA. Blood isolates: 25% isolates of Acinetobacter were sensitive to Ceftriaxone Sulbactam EDTA as compared to just 13% susceptibility for Cefoperazone+Sulbactam Urine isolates: 78% E. coli were sensitive to Ceftriaxone Sulbactam EDTA. Conclusions: The combination of ceftriaxone, sulbactam and disodium edetate was effective even against pathogens isolated from isolates from respiratory secretions, blood and urine resistant to other antibiotics.